Analysis of Disaster Risk Management in the department of Piura to adress the El Niño phenomenon - Prada-Álvarez, Aldair Edison (2024)
The objective of this research is to describe disaster risk management in the department of Piura to address the El Niño phenomenon. A qualitative approach was employed, focusing primarily on the collection of information regarding the damages and losses caused by this phenomenon, the identification of exposed zones and elements (such as population, housing, and infrastructure) susceptible to floods and landslides associated with rains from this event, as well as public spending on vulnerability reduction and emergency response to natural disasters in each province of the department of Piura in 2023. Additionally, measures were proposed to strengthen resilience, aligned with activities and investment projects that could be carried out in Piura. The provinces with the highest number of critical points with the greatest potential for flooding were Sullana, Morropón, Paita, and Piura. Moreover, in a flood risk scenario associated with El Niño rains, the provinces that have exposed elements (such as population centers, population, housing, and other infrastructures) at high to very high levels of susceptibility to flooding were Piura, Morropón, Sullana, and Sechura, while the provinces of Ayabaca and Huancabamba have exposed elements at high and very high levels of susceptibility to landslides. Additionally, of all the provinces in the department of Piura, Talara and Sechura executed less than 80% of their allocated budget for 2023. Regarding budget execution in investment projects, only the provinces of Piura and Ayabaca have executed more than 80% of their designated budget for this purpose.